Increasing Production Efficiency of Maggot with Integrated IoT Censor for Effective, Efficient, and Organized Prototype for Natural Feed in Aquaculture - Nadia Elisabet Br. Hutapea; Lisya Junus; Putri Puspita Ningrum; Hani Wahyunida Isnaini; Muchammad Zidni Ilman; Nurul Aziz; Dicky Harwanto (Journal Omni-Akuatika, 2022)
The need for feed determines 60-70% of aquaculture total production cost. Hence, the feed factor plays a very important role in performing an effective, efficient, inclusive, and sustainable aquaculture. The requirements needed to be a good cultivar are fulfilment of macronutrients and micronutrients, toxin-free, and accessible. Maggot can be used as a natural feed alternative in cultivation activities due to its sufficient nutrients content. Since 2012, aquaculture activities in Indonesia have increased alongside the rising needs for food and population growth. In this research, we conducted a research on the cultivation process of maggot by constructing three effective, efficient, and organized prototypes to achieve natural feed alternative for fish. In the first prototype, the hatching container (70x80x50 cm) will be designed with IoT censor for environmental parameter that is accessible in real time via the Blynk IoT platform. The second prototype is the vertical biopond, in which the structure and plastic container will be used to grow maggot. The structure of vertical biopond will be that of two-rack wood shelf with size specification of 80x100x34 cm. An important note to take, all designs will be created vertically. The third prototype is a 3 in 1 stall that has three components which are green net (200x150x100 cm), pupation container (30x42x15 cm), and hatching container (20x23x10 cm). All three designs can optimize the provision of economical and ecological feed that supports the fulfilment of Sustainable Development Goals in Indonesia.Keywords: Aquaculture, Black soldier fly, Internet, Natural feed, and SDGs